Community Perceptions, Concerns for Privacy, and Support for Law Enforcement Use of Aerial Surveillance in Baltimore - Nader, Elias (Crime & delinquency, 2025)
In 2020, the Baltimore Police Department implemented the Aerial Investigation Research (AIR) surveillance program, partnering with a third-party vendor that took video surveillance of the city to supporting investigations for four violent offenses: murders, non-fatal shootings, armed robberies, and carjacking. This study examined which factors shape community support for the program. Survey data was collected from Baltimore city residents online and over the phone (N?=?769). Results indicate that fear of crime and perceptions of police legitimacy and bias effect support for the AIR program. Importantly, residents who were more concerned about privacy violations were less likely to support the program and viewed it as less effective. Findings emphasize the need for police to examine public support prior to program implementation.